2001
DOI: 10.4049/jimmunol.167.3.1188
|View full text |Cite
|
Sign up to set email alerts
|

Mature Dendritic Cells Prime Functionally Superior Melan-A-Specific CD8+ Lymphocytes as Compared with Nonprofessional APC

Abstract: Priming of melan-A26/27–35-specific CTL occurs only in a fraction of late stage melanoma patients, whereas during the early stages of the disease and in healthy volunteers, melan-A CTL have functional and phenotypic markers consistent with a naive phenotype. To study the requirements for expansion of naive melan-A CTL from healthy donors, we set up an in vitro priming protocol and, using tetramer assays, we demonstrate that the activity and phenotype of the expanded melan-A CTL are profoundly influenced by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
80
0
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 72 publications
5
80
0
1
Order By: Relevance
“…In addition, processing of MHC class Irestricted antigens in endosomal compartments similar to those involved in MHC class II-restricted antigen processing was reported for DC [25,[27][28][29]. Earlier reports on the handling of antigen by DC almost exclusively relied on T cell readout systems to monitor antigen presentation [11,16,32], but these cannot discriminate between presentation of antigen and co-stimulation. A few investigators have directly analyzed the half-life of MHC molecules at the surface of DC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, processing of MHC class Irestricted antigens in endosomal compartments similar to those involved in MHC class II-restricted antigen processing was reported for DC [25,[27][28][29]. Earlier reports on the handling of antigen by DC almost exclusively relied on T cell readout systems to monitor antigen presentation [11,16,32], but these cannot discriminate between presentation of antigen and co-stimulation. A few investigators have directly analyzed the half-life of MHC molecules at the surface of DC.…”
Section: Discussionmentioning
confidence: 99%
“…Our data clearly indicate that although a large number of tumor cell lines express IDO gene, they usually do it to extents significantly lower (!100-fold lower) than those detectable in mDC. In addition, and most interestingly, it has been shown that antigen presentation by mDC, expressing IDO gene, is significantly more efficient in the induction of CTL responses in vitro and in vivo than that provided by iDC, which do not express IDO gene [12,19]. On the other hand, indirect evidence based on the use of IDO inhibitor 1-methyl tryptophan (1MT) suggests that DC activated by a combination of CD40 ligand, LPS and IFN-c may block anti-CD3 driven proliferation of total T cells [11].…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly relevant for epitopes such as melan-A 26 -35 for which even healthy donors have an atypically elevated baseline level, and for which in vitro priming cannot be excluded. 32 Indirect evidence of effector function in vaccine-driven CTL was provided by clinical findings in patient 02 (DNA/MVA), who demonstrated the highest peak of melan-A 26 -35 -specific CTL (0.19% CD8 ϩ T cells). At the same time point that the expansion of melan-A 26 -35 -specific CTL first became detectable by ex vivo tetramer analysis (day 35, 7 days after the first MVA.Mel3 injection), this patient developed redness, itching and crusting of 3 melanocytic naevi, as well as a diffuse macular rash, most prominent around the neck and shoulders.…”
Section: Immune Responses To the Recombinant Mel3 Epitopesmentioning
confidence: 99%
“…We and others have shown that HLA-A*0201-positive individuals have a higher frequency of melan-A 26 -35 -specific CTL precursors than for any of the other Mel3 epitopes. 29,30,32 Therefore, we first analyzed the frequency of melan-A 26 -35 -specific CTL by ex vivo tetramer analysis of PBMC from all 16 study time points for each patient (Fig. 2).…”
Section: Immune Responses To the Recombinant Mel3 Epitopesmentioning
confidence: 99%